Impact of organizational climate on organizational commitment and perceived organizational performance: empirical evidence from public hospitals - Aysen Berberoglu (BMC, 2018)
Abstract Background Extant literature suggested that positive organizational climate leads to higher levels of organizational commitment, which is an important concept in terms of employee attitudes, likewise, the concept of perceived organizational performance, which can be assumed as a mirror of the actual performance. For healthcare settings, these are important matters to consider due to the fact that the service is delivered thoroughly by healthcare workers to the patients. Therefore, attitudes and perceptions of the employees can influence how they deliver the service. The aim of this study was to evaluate healthcare employees' perceptions of organizational climate and test the hypothesized impact of organizational climate on organizational commitment and perceived organizational performance. Methods The study adopted a quantitative approach, by collecting data from the healthcare workers currently employed in public hospitals in North Cyprus, utilizing a self-administered questionnaire. Collected data was analyzed with the help of Statistical Package for Social Sciences, and ANOVA and Linear Regression analyses were used to test the hypothesis. Results Results revealed that organizational climate is highly correlated with organizational commitment and perceived organizational performance. Simple linear regression outcomes indicated that organizational climate is significant in predicting organizational commitment and perceived organizational performance. Conclusions There was a positive and linear relationship between organizational climate with organizational commitment and perceived organizational performance. Results from the regression analysis suggested that organizational climate has an impact on predicting organizational commitment and perceived organizational performance of the employees in public hospitals of North Cyprus. Organizational climate was found to be statistically significant in determining the organizational commitment of the employees. The results of the study provided some critical issues regarding the relationship of three concepts in the study. According to the findings, if the organizational climate scores of the employees are high, organizational commitment scores of the employees are high at the same time. In other words, if the employees in public hospitals of North Cyprus perceive the organizational climate in a positive way, they will have higher levels of organizational commitment. Findings suggested that organizational climate is an important factor in healthcare settings in terms of employee commitment and how employees perceive organizational performance, which would lead to significant results about the provision of service in healthcare organizations.